Pollution Load Estimation and Control Countermeasures of Zhangze Reservoir - Yang, Long; Zhang, Min; Wei, Jia; Qi, Jun (Frontiers in Environmental Science, 2022)
The key catchment area of Zhangze Reservoir is selected to analyze the pollution sources and identify the characteristics of the main pollution sources, aiming to provide reference for formulating targeted control countermeasures and improving the quality of water environment. Moreover, we construct an estimation method system of pollution source discharge covering point sources and non-point sources, exogenous sources and endogenous sources to estimate the discharge of pollutants from domestic sources, industrial sources, agricultural sources, sediment emission and urban runoff in Zhangze Reservoir. With the above methods, we have founded that in the study area, the annual discharge of COD, ammonia nitrogen, total nitrogen and total phosphorus are 12722.03T, 441.01T, 1616.69T and 186.90T respectively, and the annual amount of those pollutants entering the reservoir are 3157.82T, 177.62T, 760.72T and 42.29T; and according to the amount of various pollution sources into the reservoir, urban domestic sources, followed by agricultural sources, account for the largest proportion, with COD, ammonia nitrogen, total nitrogen and total phosphorus reaching 65.47%, 82.83%, 79.00% and 60.65% respectively. In addition, the total amount of main water pollutants discharged in the study area exceeds the water environmental capacity of Zhangze Reservoir, with the urban domestic sources being the biggest one. Since the pollution sources of Zhangze Reservoir are characterized by main domestic sources and coexisted by point sources, non-point sources, exogenous sources and endogenous sources, our control countermeasures should be formulated for different pollution sources to reduce the total discharge and promote the improvement of water environment quality in the basin.